Profile of Student’s Actual Competencies on Atomic Structure Topic using E-Module based on RADEC Model - Yauna, Fadhliyatul; Sopandi, Wahyu; Wahyu, Wawan (Riviera Publishing, 2023)
Atomic structure material is one of the chemistry topics that is abstract and complex. Learning topics that contain abstract and complex material requires high-level reasoning and thinking. This research aims to describe students' actual abilities in atomic structure material using an e-module based on the RADEC model. This research method is development research that adapts the Borg & Gall design. The subjects of this research were 31 students in the experimental class and 37 students in the control class. This research was conducted at one of the high schools in the city of Bandung. Students' abilities are measured through pretest questions and assignment of pretest questions. The data analysis used in this research is descriptive analysis and n-gain. This research showed that the actual competence of students in the experimental class had an n-gain of 0.58 and was in the medium category. In contrast, the actual competence of students in the control class had an n-gain of 0.29 and was in the low category. Thus, learning using e-modules based on the RADEC model can improve students' competence. The results of the student perception survey show that RADEC-based e-modules are very helpful in independent learning and completing assignments.